De Civiele Maatschappij: een 'nieuwe' partner in een 'oud' systeem - Vervisch, Thomas (Afrika Focus, 2006)
Since the 1990s, there has been a growing consensus in the international development community about the role of civil society as a relevant partner in economic development and political change all over the world. This article places this debate in the context of state-society relations in Sub-Sahara-Africa. As will become clear, the international consensus is based on one specific and highly normative interpretation of this relation between state and civil society. This consensus defines civil society as an independent actor vis-à-vis the state, capable of championing democratic and governance reforms. Our own argument starts from the assumption that this interpretation ignores the complex interrelatedness of state and civil society in African societies. As such, we propose a theoretical framework that recognizes a plurality of different state-society relations and also pays attention to informal as well as formal relations between state and civil society. By doing so, we question the international consensus about the role civil society can play in Sub-Sahara-Africa. Key Words: Civil Society, State-Society Relations, Sub-Sahara-Africa